O Camiño de Santiago e outras peregrinacións en Álvaro Cunqueiro - COSTAS, Xosé-henrique (Madrygal. Revista de Estudios Gallegos, 2010)
Álvaro Cunqueiro left traces of his fascination on the magic of Saint James’Way thorough many literary articles published in Faro de Vigo. For Cunqueiro Saint James’Way is always a metaphor of Galician and European history. The real and imaginary characters that went on pilgrimage to Compostela in Cunqueiro’s articles compose a metaphorical, achronic and fantastic composition of the entire History of mankind.
Keywords: Cunqueiro; Saint James’Way; Literary articles